Pediatric Psoriasis: A Comprehensive Review with a Focus on the Latest Therapeutic Updates - Vineet Relhan; Aneet Kaur; B. V. Priyadharshini (Indian Journal of Paediatric Dermatology)
Psoriasis is a common inflammatory disease with varied presentation ranging from papulosquamous plaques to generalized pustules. Children are also affected by this condition and it has a considerable psychological impact on both patients and their parents. There are some differences in clinical presentation and management in children when compared to adults which should be taken into account. Also, children suffering from psoriasis are at a higher risk of having metabolic syndrome as compared to the normal population, which demands screening for the same. The incidence of pediatric psoriasis is on the rise and it is crucial to make a correct diagnosis to ensure proper management. There are few studies on the management of pediatric psoriasis and the treatment guidelines are largely extrapolated from studies conducted in adults or the use of drugs for different clinical conditions in pediatric patients. In recent past, many new topical and systemic therapies have been approved for the treatment of pediatric psoriasis. In this review article, we discuss the prevalence, etiopathogenesis, clinical features, and management of pediatric psoriasis.